2011
DOI: 10.1136/hrt.2010.220228
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor is a strong predictor of mortality in patients with advanced heart failure

Abstract: HGF is a strong and independent predictor of mortality in advanced HF and, in particular, in ischaemic HF. These results indicate that HGF with its multiple effects on myocardial function exerts an overall deleterious effect in advanced HF. HGF may be of special interest for risk prediction and tailoring of HF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 30 publications
2
41
2
8
Order By: Relevance
“…Our study focused on patients with acute HF at the time of admission and also found elevated levels of HGF with a median of 1,942 pg/ml, which is more than twice the concentration in ambulatory patients and close to the values observed in patients with advanced HF. 16,17 As in the other studies, we also found a correlation with NP concentrations and renal function measures but not with LVEF, although the other studies did not include patients with preserved LVEF.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our study focused on patients with acute HF at the time of admission and also found elevated levels of HGF with a median of 1,942 pg/ml, which is more than twice the concentration in ambulatory patients and close to the values observed in patients with advanced HF. 16,17 As in the other studies, we also found a correlation with NP concentrations and renal function measures but not with LVEF, although the other studies did not include patients with preserved LVEF.…”
Section: Discussionsupporting
confidence: 65%
“…23,25 We found a significantly linear correlation between serum concentrations of cystatin C, NT-proBNP, HGF, and mortality, as in previous studies. 17,18 In the present study, we found that both HGF and NT-proBNP provide complementary information, namely that patients with both biomarkers above the median had the highest risk of death, suggesting the usefulness of this combination for refining risk stratification in acute HF. Survival time shortened as both HGF and NT-proBNP concentrations increased.…”
Section: Discussionmentioning
confidence: 78%
“…В физиологи-ческих условиях HGF находится в латентном со-стоянии и переходит в активную форму только при действии на ткани повреждающего фактора, вовле-каясь в процессы репарации и регенерации на кле-точном и тканевом уровнях [148,149]. Кроме ткани печени [150], HGF присутствует в почках [151], его концентрация в периферической крови повышается на ранних стадиях инфаркта миокарда [152,153]. Доказано, что HGF ингибирует апоптоз кардиомио-цитов на границах зоны ишемического поврежде-ния миокарда, участвует в регуляции процессов не-оангиогенеза [153].…”
Section: фактор роста гепатоцитовunclassified
“…Кроме ткани печени [150], HGF присутствует в почках [151], его концентрация в периферической крови повышается на ранних стадиях инфаркта миокарда [152,153]. Доказано, что HGF ингибирует апоптоз кардиомио-цитов на границах зоны ишемического поврежде-ния миокарда, участвует в регуляции процессов не-оангиогенеза [153].…”
Section: фактор роста гепатоцитовunclassified
“…Thus, circulating HGF levels correlate with all markers of LV remodelling after MI and are associated with re-hospitalization for heart failure. Rychli and colleagues assessed the prognostic value of HGF in heart failure in a prospective cohort study [47]. They demonstrated that the risk of all-cause mortality increases with endogenous HGF concentrations in patients with advanced HF with a 3.1-fold higher risk in the third tertile compared with the first tertile.…”
Section: Hgf As a Biomarker Of Cardiac Damagementioning
confidence: 99%